Role of the mesenchymal stromal cells in bone marrow failure of Fanconi Anemia patients - Zubicaray, Josune; Ivanova, Maria; Iriondo, June; García Martínez, Jorge; Muñoz-Viana, Rafael; Abad, Lorea; García-García, Lorena; González de Pablo, Jesús; Gálvez, Eva; Sebastián, Elena; Ramírez, Manuel; Madero, Luis; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Fanconi anemia (FA) is an inherited disorder characterized by bone marrow failure, congenital malformations, and predisposition to malignancies. Alterations in hematopoietic stem cells (HSC) have been reported, but little is known regarding the bone marrow (BM) stroma. Thus, the characterization of Mesenchymal Stromal Cells (MSC) would help to elucidate their involvement in the BM failure. Methods: We characterized MSCs of 28 FA patients (FA-MSC) before and after treatment (hematopoietic stem cell transplantation, HSCT; or gene therapy, GT). Phenotypic and functional properties were analyzed and compared with MSCs expanded from 26 healthy donors (HD-MSCs). FA-MSCs were genetically characterized through, mitomycin C-test and chimerism analysis. Furthermore, RNA-seq profiling was used to identify dysregulated metabolic pathways. Results: Overall, FA-MSC had the same phenotypic and functional characteristics as HD-MSC. Of note, MSC-GT had a lower clonogenic efficiency. These findings were not confirmed in the whole FA patients' cohort. Transcriptomic profiling identified dysregulation in HSC self-maintenance pathways in FA-MSC (HOX), and was confirmed by real-time quantitative polymerase chain reaction (RT-qPCR). Discussion: Our study provides a comprehensive characterization of FA-MSCs, including for the first time MSC-GT and constitutes the largest series published to date. Interestingly, transcript profiling revealed dysregulation of metabolic pathways related to HSC self-maintenance. Taken together, our results or findings provide new insights into the pathophysiology of the disease, although whether these niche defects are involved in the hematopoietic defects seen of FA deserves further investigation.